SPECIALIZED ASSISTANCE FOR WOMEN/GIRLS VICTIMS OF SEXUAL VIOLENCE: SERVICE PROFILE: assistência especializada às mulheres/meninas vítimas de violência sexual: perfil dos atendimentos - leidiene ferreira santos,; Michelle Tavares Barbosa dos Santos Barbosa dos Santos,; Sâmia Ponciano Gabriel Chabo,; João Pedro Sousa LIma,; Juliana Bastoni da Silva,; Danielle Rosa Evangelista, (Revista de Ciências da Saúde Nova Esperança, 2025)
Sexual violence against women is a serious public health problem. Globally, one in eight women and girls has been raped or sexually assaulted before the age of 18, representing more than 370 million people. Therefore, understanding the epidemiological profile of abuse can contribute to more effective interventions, targeting the specificities of cases and victims. Thus, this research aimed to analyze cases of violence against women and girls registered at a Specialized Care Service for People in Situations of Sexual Violence (SAVIS) in a state in the Legal Amazon between 2015 and 2023. To this end, a descriptive, quantitative, time-series, documentary-based study was conducted, approved by the Human Research Ethics Committee (CAAE 72696123.5.0000.5519). SAVIS provided 2,005 (100%) services to women victims of sexual violence from 2015 to 2023, with 2022 being the year with the highest number of reports (333; 16.6%). Over the course of nine years, 1,845 (92%) women were raped, 110 (5.5%) were harassed, and 11 (0.55%) children were subjected to pornography. The majority of abuses (1,453; 72%) occurred in the home. Regarding age group, the highest incidence was among women aged 10 to 14 (1,021; 50.4%). In the capital studied, as in other national and international settings, sexual violence primarily victimizes young women. Most aggressors are male and known to the victims. It is concluded that over the years, there has been an increase in the number of services provided to victims of sexual abuse, showing that the prevalence of violence against women/girls continues to grow and that actions to address it are weak or non-existent.